The effect of a fungicide treatment on the physiological potential of rice seeds after storage - Krüger, Fabíola de Oliveira; Guilherme, Luiz Roberto Guimarães; Franco, Daniel Fernandez; Costa, Caroline Jácome; da Silva, Márcio Gonçalves (Científica, 2016)
The chemical treatment of rice seeds before sowing causes no damage to the seed physiological potential. The objective of this study was to evaluate the physiological potential of three rice seed cultivars treated with fungicide and stored for ten months. Irrigated rice seeds cultivars BR IRGA 409, BRS Pampa and BRS Sinuelo CL produced in the season 2011/2012 treated with the fungicide carboxin + thiram were used. 3.0 kg samples of treated and untreated rice seeds were kept storing for ten months at cold chamber. After this period we assessed the physiological potential through germination, first count of germination, seedling emergence in greenhouse, cold test, length and dry mass of shoots and roots of seedlings in germination and emergence tests. The results showed that BRS Sinuelo CL cultivar was the most sensitive, while a reduction of germination percentage and germination first count after treatment and storage of seeds. The treatment of irrigated rice seeds with carboxin + thiram fungicide followed by storage of seeds for ten months is detrimental to the physiological potential of cultivar BRS Sinuelo CL. The fungicide applied together with the storage time reduces the emergence of BRS IRGA 409, BRS Pampa and BRS Sinuelo CL, as well as negatively affects the length of the root. Additional keywords: Oryza sativa L.; phytotoxicity; viability.